Peripersonal Visuospatial Abilities in Williams Syndrome Analyzed by a Table Radial Arm Maze Task - Foti, Francesca; Sorrentino, Pierpaolo; Menghini, Deny; Montuori, Simone; Pesoli, Matteo; Turriziani, Patrizia; Vicari, Stefano; Petrosini, Laura; Mandolesi, Laura (Frontiers in Human Neuroscience, 2020)
Williams syndrome (WS) is a genetic deletion syndrome characterized by severe visuospatial deficits affecting spatial exploration and navigation abilities in extra-personal space. To date, little is known about spatial elaboration and reaching abilities in the peripersonal space in individuals with WS. The present study is aimed at evaluating the visuospatial abilities in individuals with WS and comparing their performances with those of mental age-matched typically developing (TD) children by using a highly sensitive ecological version of the Radial Arm Maze (table RAM). We evaluated 15 individuals with WS and 15 TD children in two different table RAM paradigms: the free-choice paradigm, mainly to analyze the aspects linked to procedural and memory components, and the forced-choice paradigm, to disentangle the components linked to spatial working memory from the procedural ones. Data show that individuals with WS made significantly more working memory errors as compared to TD children, thus evidencing a marked deficit in resolving the task when the mnesic load increased. Our findings provide new insights on the cognitive profile of WS.